Control of electro‐osmotic flow by mixed polymer brushes: Molecular dynamics simulations. Issue 12 (30th January 2017) - Yan, Guang; Cao, Qianqian; Xin, Jingtao; Luo, Fei; Zhu, Lianqing
Abstract : Molecular dynamics simulations of electro‐osmotic flow through a channel coated by a mixed polymer brush reveal the modulation of electro‐osmotic flow. The mixed polymer brush consists of two types of neutral chains, denoted as PA and PB chains, respectively. The effect of the interaction strength between PA and PB monomers on fluid transport is studied. It was found that the PA‐PB interaction plays an important role in controlling the flow. The mixed polymer brush adopts a layered structure owing to the difference in solvent‐polymer interactions. Stronger shear force from the solvent flow leads to larger extension of polymer chains on the top layer (or PA chains). Such layering structure also causes different coupling between polymer conformational dynamics and fluid dynamics. At high grafting densities, there are remarkable differences in the velocity profiles for different PA‐PB interactions. For repulsive and attractive interactions, the increase of grafting density leads to reduced fluid transport. However, when the attraction between PA and PB interactions becomes stronger, the flow behavior is more complicated depending on the grafting density. Our simulation results indicate the change of ionic distribution induced by the conformational transition due to the PA‐PB interaction has significant contributions to the flow controlling. POLYM. ENG. SCI., 57:1293–1300, 2017. © 2017 Society of Plastics Engineers